Arl1p regulates spatial membrane organization at the trans-Golgi network through interaction with Arf-GEF Gea2p and flippase Drs2p - Tsai, Pei-Chin; Hsu, Jia-Wei; Liu, Ya-Wen; Chen, Kuan-Yu; Lee, Fang-Jen S. (Proceedings of the National Academy of Sciences - PNAS, 2013)
ADP ribosylation factors (Arfs) are the central regulators of vesicle trafficking from the Golgi complex. Activated Arfs facilitate vesicle formation through stimulating coat assembly, activating lipid-modifying enzymes and recruiting tethers and other effectors. Lipid translocases (flippases) have been implicated in vesicle formation through the generation of membrane curvature. Although there is no evidence that Arfs directly regulate flippase activity, an Arf-guanine-nucleotide-exchange factor (GEF) Gea2p has been shown to bind to and stimulate the activity of the flippase Drs2p. Here, we provide evidence for the interaction and activation of Drs2p by Arf-like protein Arl1p in yeast. We observed that Arl1p, Drs2p and Gea2p form a complex through direct interaction with each other, and each interaction is necessary for the stability of the complex and is indispensable for flippase activity. Furthermore, we show that this Arl1p-Drs2p-Gea2p complex is specifically required for recruiting golgin Imh1p to the Golgi. Our results demonstrate that activated Arl1p can promote the spatial modulation of membrane organization at the trans -Golgi network through interacting with the effectors Gea2p and Drs2p.